Influence of long-term storage on shape memory performance and mechanical behavior of pre-stretched commercial poly(methyl methacrylate) (PMMA) - Wang, Changchun (2021)
In this paper, we experimentally investigate the influence of storage at 40 °C on the shape memory performance and mechanical behavior of a pre-stretched commercial poly(methyl methacrylate) (PMMA). This is to simulate the scenario in many applications. Although this is a very important topic in engineering practice, it has rarely been touched upon so far. The shape memory performance is characterized in terms of the shape fixity ratio (after up to one year of storage) and shape recovery ratio (upon heating to previous programming temperature). Programming in the mode of uniaxial tension is carried out at a temperature within the glass transition range to one of four prescribed programming strains (namely 10%, 20%, 40% and 80%). Also investigated is the residual strain after heating for shape recovery. The characterization of the mechanical behavior of programmed samples after storage for up to three months is via cyclic uniaxial tensile test. It is concluded that from an engineering application point view, for this particular PMMA, programming should be done at higher temperatures (i.e., above its Tg of 110 °C) in order to not only achieve reliable and better shape memory performance, but also minimize the influence of storage on the shape memory performance and mechanical behavior of the programmed material. This finding provides a useful guide for engineering applications of shape memory polymers, in particular based on the multiple-shape memory effect, temperature memory effect, and/or low temperature programming.